Analysis of Influential Factors on Generation Z’s Impulsive Buying Behaviour in Context of E-Commerce Beauty Product Purchases - Jason Hartono; Josephine Patricia; Valencia Tania; Roozbeh Babolian Hendijani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the factors that influence Generation Z’s impulsive buying behaviour in the context of purchasing beauty products through e commerce platforms. The rapid growth of digital technology and online shopping has significantly changed consumer purchasing patterns, particularly among Generation Z, who are highly familiar with digital environments and social media. Impulsive buying behaviour is often triggered by various internal and external factors such as promotional offers, ease of access to online platforms, product attractiveness, and social media influence. This research uses a quantitative approach by collecting data from Generation Z consumers who have experience purchasing beauty products through e-commerce. Data were obtained through a structured questionnaire and analyzed using statistical analysis to identify the relationship between influencing variables and impulsive buying behaviour. The findings indicate that promotional strategies, product presentation, convenience of online transactions, and social influence play an important role in encouraging impulsive purchases among Generation Z consumers. Attractive discounts, limited-time offers, and visually appealing product displays on e-commerce platforms significantly increase the likelihood of unplanned purchases. In addition, recommendations from influencers and peer groups also contribute to shaping consumer decisions. Therefore, understanding these factors can help e-commerce businesses and beauty brands develop more effective marketing strategies to target Generation Z consumers while also encouraging more responsible purchasing behaviour.